2019
DOI: 10.1074/jbc.ra119.008443
|View full text |Cite
|
Sign up to set email alerts
|

The DNA deaminase APOBEC3B interacts with the cell-cycle protein CDK4 and disrupts CDK4-mediated nuclear import of Cyclin D1

Abstract: Edited by Charles E. Samuel Apolipoprotein B mRNA editing enzyme catalytic subunitlike protein 3B (APOBEC3B or A3B), as other APOBEC3 members, is a single-stranded (ss)DNA cytosine deaminase with antiviral activity. A3B is also overexpressed in multiple tumor types, such as carcinomas of the bladder, cervix, lung, head/neck, and breast. A3B generates both dispersed and clustered C-toT and C-to-G mutations in intrinsically preferred trinucleotide motifs (TCA/TCG/TCT). A3B-catalyzed mutations are likely to promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 96 publications
0
19
1
Order By: Relevance
“…Interestingly, C→T transitions have been suggested to be caused by APOBEC3B in multiple human cancers 59 . One Recent report found that APOBEC3B is capable of disrupting the CDK4‐dependent nuclear import of Cyclin D1 60 . We found that APOBEC3B affects the expression of the downstream Cyclin D1 through hypomethylation of the CCND1 promoter in cervical cancer.…”
Section: Discussionmentioning
confidence: 60%
“…Interestingly, C→T transitions have been suggested to be caused by APOBEC3B in multiple human cancers 59 . One Recent report found that APOBEC3B is capable of disrupting the CDK4‐dependent nuclear import of Cyclin D1 60 . We found that APOBEC3B affects the expression of the downstream Cyclin D1 through hypomethylation of the CCND1 promoter in cervical cancer.…”
Section: Discussionmentioning
confidence: 60%
“…Therefore, it is important to identify host factors that potentially interact with and regulate the function of A3B. Recently, hnRNP A3 and CDK4 have been suggested to interact with A3B [25,26]; however, whether these factors affect the anti-HBV function of A3B is unclear. In this research, we employed a proteomic approach to identify and comprehensively compare host factors that potentially interact with A3B in the presence of HBV, and we identified eight distinct PPI networks, including mRNA metabolism, protein folding and viral process (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins were abundant in all 6 A3B-SF data sets and, importantly, absent in GFP-SF or empty vector datasets. Only CDK4, which regulates A3B localization during the cell cycle 54 , and hnRNPUL1, which tethered to Cas9 is capable of targeting A3B for base editing 55 , had been reported previously. However, literature analyses revealed that 60% of these A3B interactors had been found independently in S9.6 AP-MS experiments 53 (Fig.…”
Section: Apobec3b Interacts With R-loops and R-loop-associated Proteinsmentioning
confidence: 99%
“…These proteins were abundant in all 6 A3B-SF data sets and, importantly, absent in GFP-SF or empty vector datasets. Only CDK4, which regulates A3B localization during the cell cycle 54 , and hnRNPUL1, which tethered to Cas9 is capable of targeting A3B for base editing 55 , 151…”
Section: Apobec3b Interacts With R-loops and R-loop-associated Proteinsmentioning
confidence: 99%